Parent perceptions regarding literacy instruction for students with intellectual disability. Issue 1 (2nd November 2020) - Wakeman, S. Y.; Pennington, R.; Cerrato, B.; Saunders, A.; Ahlgrim‐Delzell, L.
Abstract: Background: Parents offer a unique perspective as they may view literacy instruction through the lens of its direct impact on their child's daily life. Further, they are likely to provide insight into the interactions between the perceived effectiveness of instruction and their expectations for their child's success. The purposes of the current investigation were to explore perceptions of parents of children with intellectual disability (ID) related to their child's literacy instruction in schools and understand parental expectations for their child's literacy performance. Methods: In the current investigation, we surveyed 211 parents of children with ID in one state within the USA to identify their perceptions related to their child's literacy outcomes and instruction. The survey instrument contained 25 items including 9 multiple‐choice, 12 multiple‐selection, 2 open‐response and 2 rank order items. Results: Data indicated significant differences across grade bands related to the type of skills students engage in learning, the importance of specific literacy skills and the challenges or barriers for students to engage in literacy instruction. The overwhelming majority of parents reported their child learning to read as very important and believe there is a difference in life outcomes between children who can read written words and those who cannot. Parents of elementary school children report barriers of disruptive behaviour, the inability of children to remain seated and distractibility more so than parents of secondary students. Parents of high school students reported a lack of instructional time more often than parents of middle and elementary school. Conclusions: While parents across grade bands reported the importance of literacy skills for students with ID and instruction in reading comprehension, listening comprehension and vocabulary, some differences were noted. Only half the parents reported an increased focus on literacy instruction, including on essential skills (e.g. decoding), in the earlier grades. Problem behaviour and motivation served as barriers to literacy for elementary students, and a lack of instructional time served as a barrier to writing for high school students.